DO PET ANIMALS POSE A RISK OF FUNGAL INFECTIONS TO THEIR OWNERS? - DĄBROWSKA, IWONA; DWORECKA-KASZAK, BOŻENA; BIEGAŃSKA, MAŁGORZATA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Introduction: Among various microorganisms, that colonize skin of the pets, fungi, not only acts as opportunistic, but also potentially pathogenic for both humans and animals. It is expected that the closest environment of animals, their dens, collars or brushes could be the potential source of zoonotic pathogens. The aim of the study was to determine the frequency of fungi isolation from the hair coat and skin surface of healthy companion animals, their dens and from the skin of their owners’ hands. Materials and Methods: The samples were obtained in August from the healthy skin of 25 animals’ necks by brushing and 25 dens of the same animals` by swabbing and the next 25 specimens were collected from the surface of their owners hands, also with swabbing technique. All samples were cultivated and fungi were identified with routine methods. Results: A total number of 114 fungal strains, mainly mycelial fungi (93.86%) were isolated. Among them 33 isolates came from animal’s skin surface, 39 originated from the skin of owners hands. The next 42 isolates were obtained from the animals’ dens. Yeasts or yeast-like fungi were found in 6.14% of positive results of fungal growth. Dermatophytes were not isolated. The most prevalent organisms isolated from investigated samples were different species of Alternaria sp. Conclusion: The skin of healthy companion animals (pets) maybe the source of different, mainly mycelial fungi, which are opportunistic in nature. Asymptomatic carriers of dermatophytes or other pathogenic fungi were not detected among tested animals.